-3(6X+5)-2(1-17X)=3(1+5X)

Simple and best practice solution for -3(6X+5)-2(1-17X)=3(1+5X) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6X+5)-2(1-17X)=3(1+5X) equation:


Simplifying
-3(6X + 5) + -2(1 + -17X) = 3(1 + 5X)

Reorder the terms:
-3(5 + 6X) + -2(1 + -17X) = 3(1 + 5X)
(5 * -3 + 6X * -3) + -2(1 + -17X) = 3(1 + 5X)
(-15 + -18X) + -2(1 + -17X) = 3(1 + 5X)
-15 + -18X + (1 * -2 + -17X * -2) = 3(1 + 5X)
-15 + -18X + (-2 + 34X) = 3(1 + 5X)

Reorder the terms:
-15 + -2 + -18X + 34X = 3(1 + 5X)

Combine like terms: -15 + -2 = -17
-17 + -18X + 34X = 3(1 + 5X)

Combine like terms: -18X + 34X = 16X
-17 + 16X = 3(1 + 5X)
-17 + 16X = (1 * 3 + 5X * 3)
-17 + 16X = (3 + 15X)

Solving
-17 + 16X = 3 + 15X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-15X' to each side of the equation.
-17 + 16X + -15X = 3 + 15X + -15X

Combine like terms: 16X + -15X = 1X
-17 + 1X = 3 + 15X + -15X

Combine like terms: 15X + -15X = 0
-17 + 1X = 3 + 0
-17 + 1X = 3

Add '17' to each side of the equation.
-17 + 17 + 1X = 3 + 17

Combine like terms: -17 + 17 = 0
0 + 1X = 3 + 17
1X = 3 + 17

Combine like terms: 3 + 17 = 20
1X = 20

Divide each side by '1'.
X = 20

Simplifying
X = 20

See similar equations:

| w^2+3w-648=0 | | 4x-6y-6=0 | | 30r^2+19ra-63a^2= | | 50m^2+25m-3=0 | | 0.80x+0.05(16-x)=0.10(-67) | | 7x^2-47x=14 | | 15/27=X/6 | | (x+4)-(3X+3)=8 | | -16=c-6/(-3) | | 3d(d+4)= | | 6r-23=-11+2r | | 0.9z+8.25=1.5(2+2z) | | 11x^2-8x=3 | | 2x-28=-30+x | | s-8/(-8)=-1 | | V=1/3Ah | | 18/25-4/35 | | -1(x-27)+3(x+3)=9x-59 | | 24y-(y-27)=1(y-54) | | 200x^4=-800x^3+9000x^2 | | 100=-16t^2-20t+436 | | 1+4x-21x^2=0 | | 2y+7y=180 | | C=38.48+0.50x | | 2w(w+2)=0 | | 8(p-1.25)=4(2p-0.5) | | 105x^2-238x+105=0 | | x+0.5=-0.16666 | | 5+r/(-2)=-6 | | 14y^2=180 | | (2x^-3y^2)^-4/(2x^2y)^-3 | | y=-4x/1 |

Equations solver categories